Are sputum eosinophil cationic protein and eosinophils differently associated with clinical and functional findings of asthma?. Issue 5 (May 2014) - Cianchetti, S.; Bacci, E.; Ruocco, L.; Pavia, T.; Bartoli, M. L.; Cardini, C.; Costa, F.; Di Franco, A.; Malagrinò, L.; Novelli, F.; Vagaggini, B.; Celi, A.; et al.
Summary Background Sputum eosinophil counts and eosinophil cationic protein (ECP) levels are usually increased in asthmatic patients. The correlation between sputum eosinophils or ECP and clinical findings of asthma has been previously investigated but many of these studies have been performed on small samples of asthmatic patients, considering only few clinical indices and often including patients on oral or inhaled corticosteroids, which might be confounding when interpreting the relationship between disease activity and airway inflammation. Objective To assess whether sputum eosinophils and ECP were differently related to functional and clinical parameters of asthma in a large number of steroid‐naïve asthmatic patients, taking into account several potential determinants of activity and chronicity of asthma. Methods One hundred and twenty‐nine patients with mild–moderate asthma were studied. Sputum was induced by hypertonic saline inhalation and processed using the whole sample method. Results Sputum eosinophils and ECP significantly correlated with each other (r = 0.41, P < 0.001). When patients were grouped on the basis of high/low sputum eosinophils and high/low sputum ECP levels, significant differences were observed among groups, with patients with high sputum eosinophils and ECP showing the greatest asthma severity. In the overall sample, disease duration inversely correlated with sputum eosinophils, whereas FEV1 and peak expiratory flow (PEF) inversely correlated with sputum ECP. Rescue β2‐agonist use and total symptom score positively correlated with both eosinophil counts and sputum ECP. Stepwise regression analysis showed that symptom score and disease duration accounted for 17.6% of sputum eosinophil variance, whereas symptom score and FEV1 accounted for 14.7% of sputum ECP variance. Conclusions and Clinical Relevance Both sputum eosinophils and ECP are weakly related to clinical markers of asthma severity. However, ECP was more closely related to lung function parameters than eosinophil counts.